FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN PUSAT INFORMASI DAN KONSELING KESEHATAN REPRODUKSI REMAJA (PIK-R) PADA REMAJA - Yuditia Prameswari; Beril Triana (Jurnal Psikologi Poseidon, 2019)
This study was purposed to determine factors that influence students in utilizing the Youth Information and Counseling Center (PIK-R) at their school. This study uses a correlation research design with a cross sectional approach. The number of participant of this study are 36 students. Data analysis using Chi-Square techniques. The results of the study were 34 students (94.4%) had good knowledge about PIK-R, 34 students (94.4%) had positive attitudes towards PIK-R, 33 students (91.7%) had already exposed to sources of information about PIK-R, 34 students (94.4%) had used PIK-R in their daily life. Chi Square test results on knowledge variables show that there is a significant correlation between students knowledge of PIK-R, on attitude variable show that there is a significant correlation between students attitudes of PIK-R, and on exposure of information variables show that there is a significant correlation between sources of information with utilization of PIK-R.